Toll-Like Receptors, Inflammation, and Calcific Aortic Valve Disease - García-Rodríguez, Carmen; Parra-Izquierdo, Iván; Castaños-Mollor, Irene; López, Javier; San Román, J. Alberto; Sánchez Crespo, Mariano (Frontiers in Physiology, 2018)
Inflammation, the primary response of innate immunity, is essential to initiate the calcification process underlying calcific aortic valve disease (CAVD), the most prevalent valvulopathy in Western countries. The pathogenesis of CAVD is multifactorial and includes inflammation, hemodynamic factors, fibrosis, and active calcification. In the development of CAVD, both innate and adaptive immune responses are activated, and accumulating evidences show the central role of inflammation in the initiation and propagation phases of the disease, being the function of Toll-like receptors (TLR) particularly relevant. These receptors act as sentinels of the innate immune system by recognizing pattern molecules from both pathogens and host-derived molecules released after tissue damage. TLRs mediate inflammation via NF-κB routes within and beyond the immune system, and play a crucial role in the control of infection and the maintenance of tissue homeostasis. This review outlines the current notions about the association between TLR signaling and the ensuing development of inflammation and fibrocalcific remodeling in the pathogenesis of CAVD. Recent data provide new insights into the inflammatory and osteogenic responses underlying the disease and further support the hypothesis that inflammation plays a mechanistic role in the initiation and progression of CAVD. These findings make TLR signaling a potential target for therapeutic intervention in CAVD.